High-resolution molecular spectroscopy for producing ultracold absolute-ground-state 23Na87Rb molecules - Guo, Mingyang; Vexiau, Romain; Zhu, Bing; Lu, Bo; Bouloufa-Maafa, Nadia; Dulieu, Olivier; Wang, Dajun (Physical review, 2017)
We report a detailed molecular spectroscopy study of the lowest excited electronic states of 23Na87Rb for producing ultracold 23Na87Rb molecules in the electronic, rovibrational, and hyperfine ground state. Starting from weakly bound Feshbach molecules, a series of vibrational levels of the A1Σ+−b3Π coupled excited states is investigated. After resolving, modeling, and interpreting the hyperfine structure of several lines, we successfully identify a long-lived level resulting from the accidental hyperfine coupling between the 0+ and 0− components of the b3Π state, satisfying all the requirements for the population transfer toward the lowest rovibrational level of the X1Σ+ state. Using two-photon spectroscopy, its binding energy is measured to be 4977.308(3) cm−1. We calibrate all the transition strengths carefully and also demonstrate Raman transfer of Feshbach molecules to the absolute ground state.